JUSTICE MODERNIZATION IN THE DIGITAL DIVIDE OF INDONESIAN SOCIETY: A CHALLENGE - Angin, Gracious Kesuma Prinstama Perangin; Nurlaily; Seroja, Triana Dewi (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
As a developing country, Indonesia must keep abreast of and adapt to the dynamics that occur in the digital era. The government must make every effort to utilize information technology in implementing existing public policies. The Supreme Court of the Republic of Indonesia as a judicial institution that has direct contact with justice seekers has required technology-based legal services using e-court applications. The digital divide in Indonesia will greatly affect the ability of the people themselves to obtain their rights at the Indonesian judiciary. This study aims to examine whether the issuance of a judicial modernization legal policy is an appropriate law in the digital divide of Indonesian society. The method of this research uses qualitative methods based on in-depth observations of legal norms. Modernizing justice through the use of electronic applications this Indonesian society is a challenge for the government as a policymaker. This is because certain people still need assistance within their limitations in the digital world to face modern justice.